2016
DOI: 10.18632/oncotarget.8492
|View full text |Cite
|
Sign up to set email alerts
|

Associations of potentially functional variants in IL-6, JAKs and STAT3 with gastric cancer risk in an eastern Chinese population

Abstract: The interleukin-6 (IL-6)/JAK/STAT3 signaling pathway plays a central role in inflammation-mediated cancers, including gastric cancer (GCa). We evaluated associations between 10 potentially functional single nucleotide polymorphisms (SNPs) of four essential genes in the pathway and GCa risk in a study of 1,125 GCa cases and 1,221 cancer-free controls. We found that a significant higher GCa risk was associated with IL-6 rs2069837G variant genotypes [adjusted odds ratios (OR) = 1.33; 95% confidence interval (CI) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(30 citation statements)
references
References 41 publications
0
21
0
Order By: Relevance
“…Additionally, Helicobacter pylori infection is linked to an increased risk of developing gastric cancer due to alteration the expression level of IL-6 (41, 42). Furthermore, some studies have also showed that gastric cancer patients with liver metastases have higher levels of IL-6 compared to the healthy controls and high serum IL-6 level is associated with tumor invasion, tumor size and lymph node metastasis and IL-6 mediated STAT3 activation plays a crucial role in increasing tumor size and proliferation of gastric cancer (43)(44)(45)(46)(47)(48). Our results demonstrated that IL-6 and STAT3 expression level were considerably higher in cachectic gastric cancer patients levels compared to the non-cachectic and healthy control group (p < 0.01).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, Helicobacter pylori infection is linked to an increased risk of developing gastric cancer due to alteration the expression level of IL-6 (41, 42). Furthermore, some studies have also showed that gastric cancer patients with liver metastases have higher levels of IL-6 compared to the healthy controls and high serum IL-6 level is associated with tumor invasion, tumor size and lymph node metastasis and IL-6 mediated STAT3 activation plays a crucial role in increasing tumor size and proliferation of gastric cancer (43)(44)(45)(46)(47)(48). Our results demonstrated that IL-6 and STAT3 expression level were considerably higher in cachectic gastric cancer patients levels compared to the non-cachectic and healthy control group (p < 0.01).…”
Section: Discussionmentioning
confidence: 99%
“…in the cytoplasm, where it can be phosphorylated at Tyr705 via Janus kinase (JAK)-mediated tyrosine phosphorylation when stimulated by cytokines. The phosphorylated STAT3 translocates into the nucleus, combines with DNA sites, and regulates various cellular processes, including cell apoptosis and proliferation (11,12). Persistent activation of STAT3 has been observed in >70% of solid and hematological tumors, which may be one of the most notable differences between normal and malignant cells (13).…”
Section: Gallic Acid Has Anticancer Activity and Enhances The Anticanmentioning
confidence: 99%
“…Available evidence suggests that the abnormal expression of related genes plays a pivotal role in the development of gastric cancer, including tumor initiation, promotion, progression and metastasis. For example, IL‐6 and IL‐11 are important regulatory factors in the process of inflammation leading to cancer development, and they may promote tumor aggressiveness correlating with patients’ survival time . STAT3 and NF‐κB activation, which causes gastric cancer progression and leads to enhanced cellular proliferation, is also correlated with poor survival .…”
Section: Introductionmentioning
confidence: 99%